Public transport transfers assessment via transferable utility games and Shapley value approximation. Issue 4 (10th December 2021) - Gnecco, Giorgio; Hadas, Yuval; Sanguineti, Marcello
Abstract : The importance of transfer points in public transport networks is estimated by exploiting an approach based on transferable utility cooperative games, which integrates the network topology and the demands. Transfer points are defined as clusters of nearby stops, from which it is easily possible to switch between routes. The methodology is based on a solution concept from cooperative game theory, known as Shapley value. A special formulation of the game is developed for public transport networks with an emphasis on transfers. Based on such a game, the Shapley value is evaluated as an attribute of each transfer point to measure its relative importance: the greater the associated value, the larger the relevance. Due to the computational requirements of the Shapley value calculation for large-size networks, a Monte Carlo approximation is investigated and adopted. A case study of a real-world network is presented to demonstrate the model's viability.